2018
DOI: 10.1002/jmv.25321
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genotyping of enteric viruses in hospitalized children with acute gastroenteritis in Belém, Brazil: Occurrence of adenovirus viremia by species F, types 40/41

Abstract: Enteric adenovirus (AdV), sapovirus (SaV), and human astrovirus (HAstV) are important pathogens involved in the gastroenteritis etiology. In this study, a total of 219 fecal samples and sera were collected from children hospitalized for acute gastroenteritis (AGE) in two large pediatric hospitals in Belém, from March 2012 to April 2015. The samples were analyzed by polymerase chain reaction (PCR) for AdV and HAstV (astrovirus) detection, and Nested-PCR and qPCR for SaV detection. AdV was detected in 50.2% (110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
(101 reference statements)
2
21
0
Order By: Relevance
“…The available data regarding the incidence of HAdV in Brazil is limited, especially in diarrheic diseases in the post RVA vaccine era. Portal et al (2019) reported an HAdV positivity of 50.2% (110/219) in fecal samples collected from March 2012 to April 2015 from children hospitalized for AGE in two large pediatric hospitals in the Amazon region. HAdV was also detected in this study in high frequencies in both AGE and ARI groups.…”
Section: Hbga Phenotype a (N = 734)mentioning
confidence: 99%
“…The available data regarding the incidence of HAdV in Brazil is limited, especially in diarrheic diseases in the post RVA vaccine era. Portal et al (2019) reported an HAdV positivity of 50.2% (110/219) in fecal samples collected from March 2012 to April 2015 from children hospitalized for AGE in two large pediatric hospitals in the Amazon region. HAdV was also detected in this study in high frequencies in both AGE and ARI groups.…”
Section: Hbga Phenotype a (N = 734)mentioning
confidence: 99%
“…The genotype diversity detected in low-income communities may play a significant role in the burden of AGE [ 15 , 16 ], and subclinical infections and diarrhea in children seem to give a minimal degree of protection to sapovirus [ 17 ]. Children less than 5 years old living in the low-income communities of the Amazon region are highly affected by AGE, and human sapoviruses have been observed with considerable diversity [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…HAdVs are highly contagious pathogens that are known to be involved in a broad spectrum of human diseases, including respiratory diseases 5 , conjunctivitis, cystitis 6 , encephalitis 7 , and gastroenteritis 8 . Species C members are recognized as the primary pathogens responsible for respiratory tract infections among pediatric patients 911 , especially infants who are less than two years old 12 .…”
Section: Introductionmentioning
confidence: 99%